The The Influence Of Human Skill Training Of PGRI Argopuro Jember University Employees On Closing The Competency Gap And Individual Performance - Wahyu Utami, Riza (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim : This scientific article was prepared with the aim of finding out the influence of Human Skill Training on closing the competency gap and the individual performance of PGRI Argopuro Jember University employees in carrying out their job descriptions. Design/Methode/Approach : As supporting data, the authors made 58 UNIPAR Jember employees as respondents based on the results of employee assessments and performance measurements in June 2023 as a result of employee participation in Human Skill Training which was held from February to April 2023. The Human Skill Training which was held was in the form of Training on Communication Effectiveness and Increased Self-Motivation at Work. The collected data is then analyzed using regression after validity-reliability, then observing the suitability and relationship between the variables measured. From the results of employee assessments and comparisons between employee performance before and after participating in Human Skills training, it can be seen and concluded that the influence between each variable measured Research Finding : Based on the results of the analysis of the relationship between the variables tested, it can be concluded that employee participation in Human Skill Training significantly influences increasing individual competency and performance in carrying out the job description, respectively, with a sig value of 0.001 (< 0.05) and with a correlation value. (R) is 0.42 and the amount (R2) is 0.301, so it can be interpreted that the results of Human Skill Training in closing the competency and individual performance gap are 15.8%. From these conclusions it can be recommended that to improve employee competency and individual performance, Human Skill Training is needed which must also be combined with other training on Conceptual Skills and Technical Skills so that closing the competency and individual performance gaps can be achieved perfectly.